Penguatan Al-Islam Dan Kemuhammadiyahan Bagi Guru Dalam Pembentukan Karakter - Yusutria; Yuzarion; Hendra Darmawan; Sutipyo, R; Rina Febriana; Yuherman; Egi Nur Hudatun; Nimas Wening Kurniannur; Amadatul Firdausyah (Universitas Cokroaminoto Yogyakarta, 2025)
Strengthening of Islam and Muhammadiyah for teachers in character building of students at the Ibnu Juraimi Muhammadiyah Islamic Boarding School in Yogyakarta. To improve the strengthening of Islam and Muhammadiyah for teachers. This training aims to build the character of students. Strengthening was carried out on December 5 and 19, 2024. The methods used were; 1). Participatory and interactive approach. 2). Initial delivery of material. 3). Assessment and Feedback. 4). Post-training coaching and mentoring. 5). Socialization and Distribution of Results. The results of the training showed an increase in teachers' understanding in character building of students through Islam and Muhammadiyah using various strategies.